Metaphoric ramifications of the protagonists’ character, language and actions in J.M. Coetzee’s Elizabeth Costello and Slow Man - Ong'ang'a, Alfred Mugambi (Research Journal in Advanced Humanities, 2022)
This article examines the implications of the J.M. Coetzee’s employment of metaphor and metaphoric behaviour and actions of the protagonists vis-à-vis the major thematic concerns in his two novels Elizabeth Costello and Slow Man. Guided by Stylistics, the study reveals that the protagonists in the two novels, Elizabeth Costello and Paul Rayment, respectively, exhibit character, language and actions that are metaphorically allegorical to the South African apartheid and post-apartheid experiences and history. Significantly, the author’s employment of animal imagery to characterize the underprivileged position of the oppressed blacks in the South African society through the metaphorical parallels between the mass slaughtering of animals for human consumption with the extermination of the Jews by the German Nazis in Elizabeth Costello stands out clearly. The extended metaphor of the dog in the two novels to characterize the humiliating position of the oppressed brings out clearly the sense of hopelessness and destitution that the non-Whites face within the context of apartheid. The study concludes that, though the novels are set in distant places from South Africa, through the employment of animal imagery and metaphorical portrayal his protagonists in the texts, Coetzee successfully links the events in the novels to South Africa’s historical pain that is occasioned by the excruciating legacy of apartheid in the country.